PENGARUH HARGA,ULASAN PRODUK, KEMUDAHAN DAN KEAMANAN TERHADAP LOYALITAS KONSUMEN BELANJA SECARA ONLINE DI LAZADA - Onsardi, Onsardi; Putri, Untung Devomila (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2021)
This study aimed to determine the effect of price, product review, convenience and security toward consumers’ loyalty online shopping at Lazada. The population of this study were residents of the panoramic village, which amounted to 100 people. The sample of this study was taken by using the purposive sampling techniques. The data was collected by using questionnaire. The data was analyzed by using a test instrument(test validity and reliability), analysis of classical assumptions (normality, multicollinearity, and heteroscedasticity), multiple linear regression, t test and f test. Based on the results of multiple linear regression, the regression equation form Y = 3.698 -0.568 (X_1) + 0.242 (X2) + 0.724 (X3) + 0.489 (X4). Which means if the variable price (Xl), product reviews (X2), convenience (X3), security (X4) consumers’ loyalty (Y) are equal to zero, then the variable consumer loyalty will remain at 3.698. The results of the analysis of the coefficient of determination obtained a value of 0.582 or 58.2% which means that together the variables of price, product reviews, convenience and security give effect toward consumers’ loyalty, while the remaining 0.418 or 41.8% is influenced by other variables that are not included. in the research model. The results of the t-test for the price variable show the value (X2) t_hit>t_(α/2) (5.227 > 1.984) and (sig = 0.000 < 0.050). It states that the price has a negative effect toward consumers’ loyalty (Y). The review variable product (X2) shows the value of t_hit> t_(α/2) (2.045 > 1.984) and (sig = 0.044 < 0.050). It states that there is an effect of Product Reviews on Consumers’ Loyalty (Y), the convenience variable (X3) shows the value of t_hit>t_(α/2) (7.280 > 1.984) and (sig = 0.000 < 0.050). It states that there is an effect of convenience on consumer loyalty (Y), the security variable (X4) shows the value of t_hit>t_(α /2) (4.228 > 1.984) and (sig = 0.000 < 0.050). It states that there is an influence of convenience on consumer loyalty (Y). So H5 is accepted meaning price (X1), product reviews (X2), convenience (X3) and security (X2) have a positive and significant effect on consumers’ loyalty (Y) online shopping at Lazada. Keywords : Product Review, Convenience, Security, Consumers’ Loyalty.